Faktor - faktor yang yang mempengaruhi produksi kerajinan batik di Kota Jambi - Andrian Dwi Ramadan; Rahma Nurjanah; Erni Achmad (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2020)
This study aims to determine the development of labor, investment and business units in the production of the batik industry in Jambi City. This research uses quantitative data collection methods. The data used in this study is secondary data, secondary data used is a combination of periodic series (time series). In this study, it is assumed that labor, investment, and business units have a positive and significant effect on Jambi batik production in Jambi City. The data used in this study are data on labor, investment, business units, and batik production in Jambi City from 2006-2017. The data is processed using SPSS with multiple linear regression analysis methods. Keywords: Labor, Investment, Business units, Production.